2021
DOI: 10.3389/fpsyg.2021.707921
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity and Attitudes Toward Social Media Use of Active Individuals During the COVID-19 Pandemic in Saudi Arabia: Cross-Sectional Survey

Abstract: Background: Social media became an integral part of the lives of people because it encourages social relations and shares interests, activities, and real-life connections. As quarantine and lockdown orders are prolonged, many people, as well as those physically active individuals, typically responded to this stressful condition by using social media platforms.Objective: This study aimed to examine the level of physical activity of physically active individuals and their attitudes toward social media use during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 25 publications
2
6
0
1
Order By: Relevance
“…The results of this study are consistent with other research supporting the use of media technologies, such as social media platforms, to encourage physical activity during the COVID-19 pandemic [ 50 , 51 ]. Our findings add new understanding on using online social networks (i.e., Facebook friends) to promote physical activity among women during a pandemic.…”
Section: Discussionsupporting
confidence: 91%
“…The results of this study are consistent with other research supporting the use of media technologies, such as social media platforms, to encourage physical activity during the COVID-19 pandemic [ 50 , 51 ]. Our findings add new understanding on using online social networks (i.e., Facebook friends) to promote physical activity among women during a pandemic.…”
Section: Discussionsupporting
confidence: 91%
“…Alfavaz et al (11) found in their study negative effects of self-isolation and quarantine on physical activity in adults, which can be explained by the difficulties of individuals having to change their routines that were previously acquired in fitness clubs and gyms. Positive attitudes were observed in our study regarding the use of social networks ie mobile applications when performing physical exercise, as well as in the study conducted in Saudi Arabia (12). Ease of availability and a review/ selection of exercises were the most common reasons for using social networks/mobile applications in 85.1% of the surveyed population, according to our results.…”
Section: Discussionsupporting
confidence: 80%
“…Despite the positive observations found in the study conducted in Saudi Arabia as well as the influence of social media presented by the Ammar and Kaur studies, the results showed a different aspect, The level of physical activity obtained when home exercising was not sufficient to meet the regular physical activity patterns that existed before self-isolation conditions (12)(13)(14). AlMarzooki's research (12) showcased a strong relation between the attitude towards using social networks and levels of physical activity obtained. In addition, the results identified age, level of physical activity and average hours spent on social media as a significant predictors of attitudes toward their use.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…The proposed levels of physical activity are [i] inactive (low), [ii] minimally active (moderate), and [iii] health-enhancing physical activity, or a high active category (IPAQ Research Committee, 2005). Furthermore, the level of physical activity was dichotomized into moderate activity, which has >1,680 MET-min/week, and vigorous activity, whose MET-min/week was < 1,680 ( 24 26 ). The association between body image and physical activity was examined using the chi-square test analysis.…”
Section: Methodsmentioning
confidence: 99%